Violence and National History Teaching (1948 – 2006): An Institutional Colombian Perspective - Maria Isabel Cristina González (Institute of Advanced Engineering and Science, 2014)
It is possible to track multiple state reforms to secondary education in terms of curricula and syllabus throughout the second half of the twentieth century in Colombia. Underlying each reform, one can identify a rationality that surpasses the logic of Education, and is rather intertwined with the political project and ideological requirements of the government in office, or with certain socio-political junctures. The impact of the political world on education is particularly noticeable in school subjects that address National History. Within this perspective it is shown how, after institutional changes have occurred, different memories and visions about citizenship, democracy, conflict and nation are being promoted. This highlights different ways of subordination of the educational project to a wide universe of political dynamics.DOI: http://dx.doi.org/10.11591/ijere.v3i4.6795